2013
DOI: 10.1007/978-1-62703-278-0_14
|View full text |Cite
|
Sign up to set email alerts
|

VIGS: A Tool to Study Fruit Development in Solanum lycopersicum

Abstract: A visually traceable system for fast analysis of gene functions based on Fruit-VIGS methodology is described. In our system, the anthocyanin accumulation from purple transgenic tomato lines provides the appropriate background for fruit-specific gene silencing. The tomato Del/Ros1 background ectopically express Delila (Del) and Rosea1 (Ros1) transgenes under the control of fruit ripening E8 promoter, activating specifically anthocyanin biosynthesis during tomato fruit ripening. The Virus-Induced Gene Silencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…This alternative technology could provide a rapid tool for the functional analysis of the genes of interest (transgenes) (Wróblewski et al 2005). An important breakthrough in the fast reverse genetics was achieved by using a powerful tool-virus induced gene silencing (VIGS) technology Fernandez-Moreno et al 2013). Jaberolansar et al (2010) and Romero et al (2011) successfully demonstrated that the Tobacco Rattle Virus (TRV)-based VIGS vector could be used in tomato to silence genes.…”
Section: Methods Of Tomato Transformationmentioning
confidence: 99%
“…This alternative technology could provide a rapid tool for the functional analysis of the genes of interest (transgenes) (Wróblewski et al 2005). An important breakthrough in the fast reverse genetics was achieved by using a powerful tool-virus induced gene silencing (VIGS) technology Fernandez-Moreno et al 2013). Jaberolansar et al (2010) and Romero et al (2011) successfully demonstrated that the Tobacco Rattle Virus (TRV)-based VIGS vector could be used in tomato to silence genes.…”
Section: Methods Of Tomato Transformationmentioning
confidence: 99%
“…VIGS is one of the most widely used genomic tools, displaying several advantages such as allowing easy and rapid gene silencing, with no need for stable plant transformation, and enabling both forward and reverse genetic approaches in many crop species (Senthil-Kumar and Mysore, 2011). VIGS has been successfully used to better define the role of genes involved in various plant processes including fruit development (Fernandez-Moreno et al, 2013) or abiotic stress tolerance (Ramegowda et al, 2014).…”
Section: Virus-derived Technologiesmentioning
confidence: 99%
“…Such an approach can assure fast implementation of the functional analysis of the genes of interest (GOI) (Wróblewski et al 2005;Fernandez et al 2009). Fundamental progress in rapid reverse genetics was accomplished by employing RNAi (RNA interference) strategy (Orzaez and Granell 2009;Fernandez-Moreno et al 2013). In plants, RNAi can be induced in two ways: by a transgene (TIGS, transgene induced gene silencing) or a virus (VIGS, virus-induced gene silencing).…”
Section: Methodology Of Tomato Transformationmentioning
confidence: 99%